PERAN GURU DALAM MEMPERTAHANKAN BUDAYA INDONESIA UNTUK MEMBENTUK KARAKTER SISWA DI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) - Ahsani, Eva Luthfi Fakhru; Ni’mah, Nahdlotun; Rifqiyani, Lailatul; Rahmawati, Putri; Auliya, Rikzatul (Eduscience : Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the role of teachers in maintaining Indonesian culture to shape the character of students at Kuala Lumpur Indonesian School. This research was conducted because seeing the current condition of many young people leaving Indonesian culture due to the swift currents of globalization. The method used in this study is a qualitative method with literature study techniques. The study conducted studies with journals and books on the formation of character and cultural values that were instilled in learning at the Kuala Lumpur Indonesian School. The results of this study indicate that the teaching staff at the Kuala Lumpur Indonesian School is very strong in maintaining Indonesian culture to shape the character of students through learning activities, extracurricular activities which include dance, traditional musical instruments and so on. There are several characters that are applied at the Kuala Lumpur Indonesian School, including honesty, discipline, love of culture, and love of the country. With this activity, students at Kuala Lumpur Indonesian School do not lose their character as Indonesian citizens and can know and be able to preserve Indonesian culture in the international arena. Keywords: The Role of Teachers, Indonesian Culture, Shaping Character